1980
DOI: 10.1084/jem.151.4.839
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and release of erythroid colony- and burst-potentiating activities by purified populations of murine peritoneal macrophages

Abstract: We investigated the effects of murine resident peritoneal macrophages on the in vitro proliferation of erythropoietin (Ep)-sensitive committed precursors colony-forming unit-erythroid (CFU-E) and burst-forming unit-erythroid (BFU-E) with a two-layer cloning system of methylcellulose and semisolid agar. The addition of increasing numbers of macrophages to the agar underlayer resulted in a progressive increase in the numbers of both CFU-E and BFU-E that proliferated in the presence of Ep. CFU-E, but not BFU-E, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…These experiments and previous reports of BPA in media conditioned by monocytes or macrophages (7,8,11,35) suggest that monocytes are capable of producing all the BPA or other factors necessary for optimal proliferation and differentiation of human BFU-E in vitro. However, the possibility that T lymphocytes also are capable of producing small quantities of BPA has not been excluded.…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…These experiments and previous reports of BPA in media conditioned by monocytes or macrophages (7,8,11,35) suggest that monocytes are capable of producing all the BPA or other factors necessary for optimal proliferation and differentiation of human BFU-E in vitro. However, the possibility that T lymphocytes also are capable of producing small quantities of BPA has not been excluded.…”
Section: Resultssupporting
confidence: 49%
“…Burst-promoting activity (BPA), which is a proposed regulator of the proliferation and initial stages of differentiation of BFU-E, has been detected in media conditioned by unstimulated, mitogenstimulated, or antigen-stimulated unfractionated mononuclear cells (4-8, 10, 15-18), monocytes or macrophages (7,8,11,34), or T lymphocytes (7,9,10,12,15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some studies showed that the erythroid co lony (BFU-E) growth is not regulated necessarily by erythropoietin, but by cells such as T lymphocytes or monocytes and BFU-E interaction [4][5][6].…”
Section: Introductionmentioning
confidence: 99%